HIFDZUDDIN AND THE GUARANTEE OF FREEDOM OF INDIGENOUS BELIEF ON INDONESIAN IDENTITY CARD/KTP - Syaifullahil Maslul (IAIN Bone, 2020)
Indigenous faith followers/believers receive discriminatory acts. This is as regulated in Article 61 paragraph (1), paragraph (2) and Article 64 paragraph (1), paragraph (5) of the Population Administration Law. In this regulation, for followers of belief, the religion column is not filled because it is not recognized by the state. The discriminatory treatment in the Population Administration Law is then submitted for a judicial review to the Constitutional Court. This writing questions the decision of the Constitutional Court Number 97 / PUU-XIV / 2016 from two aspects, Hifdzuddin and Guarantee of Freedom of Belief. This writing is writing normative law with a conceptual approach (conceptual approach) and a statutory approach. The result of this writing, the decision of the Constitutional Court Number 97 / PUU-XIV / 2016 is in accordance with the concept of hifdzuddin with respect for followers of other religions and beliefs. Besides that, this decision is also in accordance with the concept of guaranteeing freedom of belief in accordance with the 1945 Constitution.